Answer:
A (-2x+3)
Explanation:
The slope-intercept form of a linear equation is y = mx+b. M being the slope and b being the y-intercept. We know the slope is -2, so we have y = -2x+b. If point E is at (1,1), we can use that to get our y-intercept (where x=0). That point would be (0,3) since a negative slope increases the farther left along the x-axis you go and has an absolute value of 2, thereby increasing by 2 for every 1 travelled along the x-axis. (0,3) is the y-intercept thus we get y = -2x+3.